Identification and characterization of compounds from Chrysosporium multifidum, a fungus with moderate antimicrobial activity isolated from Hermetia illucens gut microbiota - Correa Y. (2019)
The gut microbiota of insects is composed of a wide range of microorganisms which produce bioactive compounds that protect their host from pathogenic attack. In the present study, we isolate and identify the fungus Chrysosporium multifidum from the gut of Hermetia illucens larvae. Extract from C. multifidum culture broth supernatant showed moderate activity against a strain of methicillin-resistant Staphylococcus aureus (MRSA). Bioguided isolation of the extract resulted in the characterization of six ?-pyrone derivatives (1-6) and one diketopiperazine (7). Of these compounds, 5,6-dihydro-4-methoxy-6-(1-oxopentyl)-2Hpyran- 2-one (4) showed the greatest activity (IC50 = 11.4 ± 0.7 ?g/mL and MIC = 62.5 ?g/ mL) against MRSA. © 2019 Correa et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.